De Collectie : aankopen Stadsgalerij Heerlen 1986-1991. (Heerlen : Stadsgalerij, 1991)
Armando ; Birza, Rob ; Breedveld, Marian ; Content, Eli ; Drummen, Suzan ; Dumas, Marlene ; Gerritsen, Ad ; van Haaften, Joost ; Haagmans, Fons ; Hermans, Benoît ; Hermens, Bert ; Hoekstra, Berend ; Hohenbüchler, Irene ; Huisman, Michel ; Janssen, Edwin ; Killaars, Fransje ; van Koningsbruggen, Rob ; van de Kop, David ; Lucassen ; Molin, Lei ; Sierhuis, Jan ; Slits, Ton ; Smits, Kees ; Stoop, Pieter ; Swennen, Walter ; Teeken, Toon ; Verkerk, Emo ; Villevoye, Roy ; Wehrens, Peter ; Zoetbrood, Jean-Pierre
De Collectieaankopen Stadsgalerij Heerlen 1986-1991, Stadsgalerij, Heerlen, 18 januari t/m 10 mei 1992
boek